A NOTE ON THE GENERAL TREND OF MARINE FISH CATCHES IN INDIA - Banerji, S.K.; Satyanarayana, V.V. (Indian Journal of Fisheries, 2015)
The purpose of this note is to present briefly the trend of marine fish catches in India during the post-1950 period, and to compare it with the available statistics for the period prior to 1950. Excepting for the rough estimates given in the Report on the Marketing of Fish in the Indian Union (Government of India, 1951) no other statistics on an all-India basis are available before 1950. The catch statistics on marine fisheries for the post-1950 period have been taken from the Fishery Survey and Statistics Section of Central Marine Fisheries Reseasch Station which is engaged in the collection of such statistics since 1950.